2019
DOI: 10.1101/632760
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comprehensive knowledge base of synaptic electrophysiology in the rodent hippocampal formation

Abstract: The cellular and synaptic architecture of the rodent hippocampus has been described in thousands of peer-reviewed publications. However, no human- or machine-readable public catalog of synaptic electrophysiology data exists for this or any other neural system. Harnessing state of the art information technology, we have developed a cloud-based toolset for identifying empirical evidence from the scientific literature pertaining to synaptic electrophysiology, for extracting the experimental data of interest, and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…The underlying synapse model consisted of several parts, each with their associated parameters, which we determined in a six‐step procedure: We modeled synaptic connections with biexponential conductances requiring 8 parameters. Three parameters ( E rev , τ rise , τ decay ) were directly obtained from the literature (see Supplementary Table S1 for AMPAR and GABAR rise and decay time constants, methods for NMDAR time constants, and Supplementary Table S2 for reversal potentials (Moradi & Ascoli, 2020)). In particular, for the τ decay (Supplementary Table S1) with the exception of Maccaferri, Roberts, Szucs, Cottingham, and Somogyi (2000) who used either single or weighted biexponential fits, none of the other studies we considered explicitly reported how τ decay was extracted.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The underlying synapse model consisted of several parts, each with their associated parameters, which we determined in a six‐step procedure: We modeled synaptic connections with biexponential conductances requiring 8 parameters. Three parameters ( E rev , τ rise , τ decay ) were directly obtained from the literature (see Supplementary Table S1 for AMPAR and GABAR rise and decay time constants, methods for NMDAR time constants, and Supplementary Table S2 for reversal potentials (Moradi & Ascoli, 2020)). In particular, for the τ decay (Supplementary Table S1) with the exception of Maccaferri, Roberts, Szucs, Cottingham, and Somogyi (2000) who used either single or weighted biexponential fits, none of the other studies we considered explicitly reported how τ decay was extracted.…”
Section: Resultsmentioning
confidence: 99%
“…In the continuing spirit of bringing together, hippocampal synaptic electrophysiology from published literature a recent complementary study leveraged text‐mining techniques to extract the properties of synaptic connections in hippocampal CA1, including PSP amplitudes and peak conductances (Moradi & Ascoli, 2020). The authors have also open‐sourced their collection of papers and parameters alongside useful cloud‐based tools to calculate reversal potentials and LJPs, of which we took advantage for this paper.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The functional importance of synaptic physiology in the hippocampus, coupled with the ease of stimulating the anatomically segregated pathways in different layers of the hippocampus such as stratum radiatum, led to an explosion of data on the synaptic physiology of the hippocampus. A catalog of this massive database of synaptic physiology is described in the special issue article by Moradi and Ascoli (). This article provides a framework to allow computational modelers to access the broad database of physiological experiments and constrain the parameters of detailed biophysical models.…”
Section: Introductionmentioning
confidence: 99%